Mendorong Gerakan Keluarga Sadar Gizi Menuju Keluarga Sehat dan Produktif di Desa Argo Mulyo, Kecamatan Sepaku, Kalimantan Timur - Khuzaimah, Ummi (Jurnal Abdita Naturafarm, 2024)
This community service aims to provide understanding to housewives regarding efforts to build nutrition-conscious family behavior (KADARZI). It is hoped that this can encourage improvements in the quality of household health by forming healthy and productive families. Forming a nutritionally aware family can reduce the risk of health problems, especially those related to nutritional problems in family members. The method of implementing community service is carried out through 'socialization' activities. Partners in this activity are the Argo Mulya Village Community, Sepaku District, North Panajam Paser Regency, East Kalimantan Province. The number of housewives who participated in the activity was 33 people with children under five and school age. It is hoped that the results of this activity can increase nutrition-conscious behavior starting at the household level in Argo Mulyo Village, Sepaku District.